Applying the CiPA approach to evaluate cardiac proarrhythmia risk of some antimalarials used off‐label in the first wave of COVID‐19 - Delaunois, A; Abernathy, M; Anderson, WD; Beattie, KA; Chaudhary, KW; Coulot, J; Gryshkova, V; Hebeisen, S; Holbrook, M; Kramer, J; Kuryshev, Y; Leishman, D; et al. (Wiley, 2021)
We applied a set of in silico and in vitro assays, compliant with the CiPA (Comprehensive In Vitro Proarrhythmia Assay) paradigm, to assess the risk of chloroquine or hydroxychloroquine‐mediated QT prolongation and Torsades de Pointes (TdP), alone and combined with erythromycin and azithromycin, drugs repurposed during the first wave of COVID‐19. Each drug or drug combination was tested in patch clamp assays on 7 cardiac ion channels, in in silico models of human ventricular electrophysiology (Virtual Assay®) using control (healthy) or high‐risk cell populations, and in human induced pluripotent stem cell (hiPSC)‐derived cardiomyocytes. In each assay, concentration‐response curves encompassing and exceeding therapeutic free plasma levels were generated. Both chloroquine and hydroxychloroquine showed blocking activity against some potassium, sodium and calcium currents. Chloroquine and hydroxychloroquine inhibited IKr (IC50: 1µM and 3‐7µM, respectively) and IK1 currents (IC50: 5 and 44µM, respectively). When combining hydroxychloroquine with azithromycin, no synergistic effects were observed. The two macrolides had no or very weak effects on the ion currents (IC50>300‐1000µM). Using Virtual Assay®, both antimalarials affected several TdP indicators, chloroquine being more potent than hydroxychloroquine. Effects were more pronounced in the high‐risk cell population. In hiPSC‐derived cardiomyocytes, all drugs showed early‐after‐depolarizations, except azithromycin. Combining chloroquine or hydroxychloroquine with a macrolide did not aggravate their effects. In conclusion, our integrated nonclinical CiPA dataset confirmed that, at therapeutic plasma concentrations relevant for malaria or off‐label use in COVID‐19, chloroquine and hydroxychloroquine use is associated with a proarrhythmia risk, which is higher in populations carrying predisposing factors but not worsened with macrolide combination.